2020
DOI: 10.5371/hp.2020.32.3.142
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ultrasound-guided Single-injection Triple Nerve Block Before Cementless Bipolar Hip Hemiarthroplasty in Femoral Neck Fractures

Abstract: Purpose: To compare efficacy of ultrasound (US)-guided single-injection nerve blocks (SINB) before bipolar hemiarthroplasty (BHA) of the hip in patients with femoral neck fractures. Materials and Methods: Clinical outcomes of 89 patients who underwent BHA between September 2016 and February 2018 were retrospectively compared. Eight patients were excluded according to exclusion criteria and the remaining patients were divided into two groups: patients who received SINB before surgery (Group I; n=40), and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
2
13
1
Order By: Relevance
“…Our report is similar to reports of previous authors where regional anaesthesia was able to be used as a safe and satisfactory alternative anaesthetic technique in a critically ill patient requiring lower limb amputation surgery 12 13. As the duration of the nerve blocks can last for 24 hours, their analgesic effect can reduce immediate postoperative pain, opioid consumption and their related side effects 14 15. This was seen in our case as well including other postoperative outcomes such as reduced 30-day mortality and morbidity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our report is similar to reports of previous authors where regional anaesthesia was able to be used as a safe and satisfactory alternative anaesthetic technique in a critically ill patient requiring lower limb amputation surgery 12 13. As the duration of the nerve blocks can last for 24 hours, their analgesic effect can reduce immediate postoperative pain, opioid consumption and their related side effects 14 15. This was seen in our case as well including other postoperative outcomes such as reduced 30-day mortality and morbidity.…”
Section: Discussionsupporting
confidence: 90%
“…This was seen in our case as well including other postoperative outcomes such as reduced 30-day mortality and morbidity. In case, the effects of the nerve blocks are needed for more than 24 hours, serial nerve block injections or continuous nerve blockade catheters can be considered 16…”
Section: Discussionmentioning
confidence: 99%
“…Under US guidance, the femoral (3-in-1 block) [ 3 ] and sciatic nerve (posterior popliteal approach) [ 4 ] were each blocked using 7.5 and 8 ml respectively, of 0.75% ropivacaine mixed with 7.5, 8 ml of 1% lidocaine at a 1:1 ratio (Fig. 2 ) [ 7 ]. A sensory test including a pinprick test was done after performing the block to confirm a successful block.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] Peripheral nerve block (PNB) is the recommended multimodal pain management for patients undergoing BHA. [16][17][18][19][20] Pain management after hip-fracture surgery in geriatric patients not only results in diminished pain, but also in diminished complications that could be caused by pain. However, most studies of multimodal pain management only focused on patient-reported subjective outcomes (e.g., visual analog scale (VAS)).…”
Section: Introductionmentioning
confidence: 99%